2015
DOI: 10.1093/neuonc/nov012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative HER2 and p95HER2 levels in primary breast cancers and matched brain metastases

Abstract: This is the first study of quantitative p95 and HER2 expression in matched PBC and BM. BM of breast cancer shows significant increases in expression of both biomarkers compared with matched PBC. These data provide a rationale for future correlative studies on p95 and HER2 levels in BM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…We postulate that the neuregulin‐rich brain microenvironment also contributes to therapeutic resistance in BMs. HER2 and HER3 are induced in BMs from breast and lung cancers and our data suggest that this is an adaptive response to paracrine ligands (see supplementary material, Figure S13), since most BMs lacked expression of NRG RNA. Neuregulin‐1 mediates resistance to cisplatin therapy in mouse models of non‐small cell lung cancer and this may also be relevant in BMs, which are essentially treatment‐refractory manifestations of cancer arising in a neuregulin‐rich microenvironment.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We postulate that the neuregulin‐rich brain microenvironment also contributes to therapeutic resistance in BMs. HER2 and HER3 are induced in BMs from breast and lung cancers and our data suggest that this is an adaptive response to paracrine ligands (see supplementary material, Figure S13), since most BMs lacked expression of NRG RNA. Neuregulin‐1 mediates resistance to cisplatin therapy in mouse models of non‐small cell lung cancer and this may also be relevant in BMs, which are essentially treatment‐refractory manifestations of cancer arising in a neuregulin‐rich microenvironment.…”
Section: Discussionmentioning
confidence: 77%
“…There is a growing body of literature implicating the ERBB /HER pathway activation in development of BMs . Therefore, taking a candidate approach, we analysed mutation, copy‐number and expression of key ERBB /HER pathway members (Figure A; see also supplementary material, Figures S5, S6, S9, S10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that several primary breast cancers, originally negative for HER2, were HER2 positive after metastasizing to the brain (6).Quantitative analysis of matched primary and BCBM tumors for HER2 and truncated HER2 (p95HER2) showed that there was a 2.1 fold increase in HER2 and a 1.5 fold increase in p95HER2 expression from the primary breast tumor to the brain metastasis (111). Additionally, CTCs from BCBM patients were assessed for HER2 expression by antibody based analysis and RT-PCR.…”
Section: Correlative Studiesmentioning
confidence: 99%
“…Quantitative analysis of matched primary and BCBM tumors for HER2 and truncated HER2 (p95HER2) showed that there was a 2.1 fold increase in HER2 and a 1.5 fold increase in p95HER2 expression from the primary breast tumor to the brain metastasis (111). Additionally, CTCs from BCBM patients were assessed for HER2 expression by antibody based analysis and RT-PCR.…”
Section: Role Of Her2 In Breast Cancer Brain Metastasismentioning
confidence: 99%